2013
DOI: 10.1111/nph.12376
|View full text |Cite
|
Sign up to set email alerts
|

Labile compounds in plant litter reduce the sensitivity of decomposition to warming and altered precipitation

Abstract: SummaryTogether, climate and litter quality strongly regulate decomposition rates. Although these two factors and their interaction have been studied across species in continent-scale experiments, few researchers have studied how labile and recalcitrant compounds interact to influence decomposition, or the climate sensitivity of decomposition, within a litter type.Over a period of 3 yr, we studied the effects of warming and altered precipitation on mass loss and compound-specific decomposition using two litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 68 publications
2
59
0
2
Order By: Relevance
“…Despite extensive work on the subject, the degree to which C chemistry alone drives the decomposition of litter and soil in response to elevated temperatures is frequently debated (Giardina and Ryan, 2000;Bol et al, 2003;Fierer et al, 2005;Knorr et al, 2005;Bauer et al, 2008;Conant et al, 2008;Craine et al, 2010;Hopkins et al, 2012;Suseela et al, 2013;Lefevre et al, 2014), as is the response of soil-C to N addition (Melillo et al, 2002;Neff et al, 2002;Auyeung et al, 2013). Part of this confusion may lie in the impact and influence of microbial community structure and function, as it has been shown as a potential driver of soil C turnover in response to N (Billings and Ziegler, 2008;Chen et al, 2014;Kaiser et al, 2014), warming (Bardgett et al, 2008;Balser and Wixon, 2009;Yuste et al, 2011;Zhou et al, 2012;Nie et al, 2013;Ziegler et al, 2013;Hopkins et al, 2014;Wei et al, 2014), and the interactive effects of N and warming (Cusack et al, 2010;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive work on the subject, the degree to which C chemistry alone drives the decomposition of litter and soil in response to elevated temperatures is frequently debated (Giardina and Ryan, 2000;Bol et al, 2003;Fierer et al, 2005;Knorr et al, 2005;Bauer et al, 2008;Conant et al, 2008;Craine et al, 2010;Hopkins et al, 2012;Suseela et al, 2013;Lefevre et al, 2014), as is the response of soil-C to N addition (Melillo et al, 2002;Neff et al, 2002;Auyeung et al, 2013). Part of this confusion may lie in the impact and influence of microbial community structure and function, as it has been shown as a potential driver of soil C turnover in response to N (Billings and Ziegler, 2008;Chen et al, 2014;Kaiser et al, 2014), warming (Bardgett et al, 2008;Balser and Wixon, 2009;Yuste et al, 2011;Zhou et al, 2012;Nie et al, 2013;Ziegler et al, 2013;Hopkins et al, 2014;Wei et al, 2014), and the interactive effects of N and warming (Cusack et al, 2010;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3). Although some studies showed greater losses of lignin at higher temperatures Suseela et al, 2013), consistent with greater temperature sensitivity of kinetically stable compounds, both increases (Derenne and Largeau, 2001) and decreases (Dignac et al, 2005;Klotzbücher et al, 2011;Thevenot et al, 2010) in lignin (or aryl C) were observed in response to decomposition. The proportional increase in lignin C with temperature in this experiment was likely driven by factors other than chemical complexity.…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies have shown that starting litter chemistry and microbial community structure shape OM losses in response to temperature (Karhu et al, 2014;Suseela et al, 2013), and impact the composition of residual OM (Wallenstein et al, 2013;Wickings et al, 2012). Therefore, we hypothesized that starting OM complexity and microbial community structure, rather than temperature, would shape compositional changes in OM during incubation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The relative peak heights were computed as the ratio of the intensity of each peak to the sum of the intensities of all selected peaks (Haberhauer and Gerzabek 1999). We conducted a principal component analysis (PCA) of the relative peak heights to interpret the DRIFT spectra (Suseela et al 2013).…”
Section: Litter Chemistry Analysesmentioning
confidence: 99%